Plate laser beam splitter with mixture-based quarter-wave coating design. (November 2022) - Du, Wenyun; Zhu, Meiping; Shi, Jun; Liu, Tianbao; Zeng, Tingting; Sun, Jian; Yi, Kui; Shao, Jianda
Abstract: Plate laser beam splitter (PLBS) coatings for intensity-splitting in high-power laser applications face increasing requirements, where the challenge is to simultaneously satisfy a given transmittance (T)/reflectivity (R) intensity-splitting ratio with a certain bandwidth, and a high laser damage threshold (LIDT). Traditionally, a given T/R ratio is achieved by using a non-quarter-wave design. We propose a quarter-wave design strategy for arbitrary T/R ratios by using mixture layers with tunable refractive index ( n ) and optical bandgap as high- n layers. Two quarter-wave PLBS coatings based on HfO2 –Al2 O3 mixture with a designed T/R ratio of 50:50 are experimentally demonstrated and compared with the traditional PLBS coating. The mixture-based PLBS coating shows good spectral performance, low surface roughness, and high LIDT. For an s -polarized 8 ns pulse laser at a wavelength of 1064 nm, a mixture-based PLBS coating design can improve LIDT by a factor of ∼ 2 with a slightly wider bandwidth. This tunable mixture-based PLBS coating design strategy provides support for the increasingly high output power of high-power laser systems.